A formação continuada de professores do ensino comum no campo da educação especial - Kautsky, Giselle Lemos Schmidel (2016)
This project systematized reflections resulting from a research, aiming to analyze a continuing education developed in an extension course, involving teachers who worked with a target group of special education students in regular education. This is a qualitative research, designed as research-formation. The data collected through questionnaires, records in field diary, interviews and legal documents guiding the municipal, state and private education systems. It is supported analyzes on the presuppositions of cultural-historical perspective and as well in Sociology Figurational, developed by Norbert Elias. In the results, can observe that the everyday practice of the Schools shall characterized by objective questions that hinder the teaching. Thereby teacher education needs to be an invitation to reflect on the school, its internal policy and its operation. As well appears that, although teachers should not restrict their practices to specific knowledge in teacher training spaces for the common room, access to guidance regarding the use of technologies and methodologies that qualify and boosting the education of the students public-target from Special Education has absolutely pertinent